Evaluation of Solid Brain Metastases in Lung Cancers with Diffusion MRI [Akciger Kanserli Hastalarda Solid Beyin Metastazlarinin Difuzyon MRG ile Degerlendirilmesi] - Ismail Okan Yildirim; Ayse Aktas (Medicine Science, 2014)
The primary malignant tumors that mostly metastasis to the brain are lung cancers, breast cancers, colorectal cancers, renal cell cancer and malanomas. The most important factors that act in the planning and the prognosis of lung cancers are cellular type and staging. Tumors have different metastasis power with respect to the histologic types. The ADC values obtained from the diffusion weighted imaging in brain tumors were evaluated as the basic marker of the tumor cellularity. The aim of this study is to compare the quantitative ADC values in solid brain metastases with lung cancer cases according to the histologic types, solidarity and multiplicity using diffusion weighted images. In our study, the ADC and the metastatic ADC values were compared with normal parenchyma according to the histopathologic types regarding the edema around the metastasis of the brain, but a statistically significant difference was not detected. However, in cases with multiple brain metastases had lower ADC values and rates when compared with single metastases and it was found statistically significant. In conclusion, the tumor cellularity of the brain metastases in lung cancers may be independent from histopathologic diagnosis, and that the detection of lower ADC values in multiple metastases when compared with single metastases makes us think that multiple metastases have higher degree of tumor cellularity. These findings demonstrate that in lung cancer cases with multiple metastases, the tumor grade would be more important and that the lower ADC values would be due to this situation. [Med-Science 2014; 3(1.000): 1079-91]